APPROACH TO VALUES EDUCATION AS A LEARNING FRAMEWORK FOR ISLAMIC RELIGIOUS EDUCATION - Cahaya; Agung Putra Mulyana; Muhammad Kharizmi; Muhammad Irfan (International Journal of Teaching and Learning, 2024)
Values  education          is            essentially          humanizing       humans,              forming              a generation of people who are superior and have humanist, intellectual and spiritual personalities. In reality, now education cannot maximize its role in shaping students' values, the negative influence of the environment and the progress of globalization have also shifted the level of students' values from time after time so that moral degradation becomes increasingly unstoppable, a social disease that increasingly colors the world of education and the scope of society. Learning Islamic Religious Education can be interpreted as an effort to make students able to learn, encouraged to learn, willing to learn and interested in continuing to study Islam as a whole which results in several relatively permanent changes in a person's behavior both cognitively, effectively and psychomotorically. The approaches to values education as a learning framework are the values instillation approach, the cognitive moral development approach, the values analysis approach, the values classification approach, and the learning to do approach. This value education approach can be said to be a very appropriate approach in implementing education (PAI learning). One reason is related to the aim of education regarding instilling certain values in students.